2020
DOI: 10.2337/dc20-0924
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis and Related Events With Sotagliflozin Added to Insulin in Adults With Type 1 Diabetes: A Pooled Analysis of the inTandem 1 and 2 Studies

Abstract: OBJECTIVE To evaluate the incidence and risk factors for diabetic ketoacidosis (DKA) and related adverse events (AEs) in adults with type 1 diabetes treated with sotagliflozin adjunctive to insulin. RESEARCH DESIGN AND METHODS Data from two identically designed, 52-week, randomized studies were pooled and analyzed for DKA, changes in β-hydroxybutyrate (BHB), and percentage of patients with BHB >0.6 and >1.5 mmol/L. The patients were administered placebo, sotagliflozin 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“… 19 , 30 An increased risk of diabetic ketoacidosis has only been observed with sotagliflozin, specifically in patients with type 1 diabetes. 21 The adverse event profile is generally consistent with other SGLT inhibitors. In the present study, none of these AEs was observed in Chinese healthy subjects.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“… 19 , 30 An increased risk of diabetic ketoacidosis has only been observed with sotagliflozin, specifically in patients with type 1 diabetes. 21 The adverse event profile is generally consistent with other SGLT inhibitors. In the present study, none of these AEs was observed in Chinese healthy subjects.…”
Section: Discussionsupporting
confidence: 62%
“… 18 , 19 However, sotagliflozin is associated with the following adverse reactions including diarrhoea, genital mycotic infections, urinary tract infections, hypotension/volume depletion, increased serum creatinine and decreased estimated glomerular filtration rate (eGFR) occurred after initiating sotagliflozin, and especially diabetic ketoacidosis (in patients with type 1 diabetes). 13 , 19 , 21 , 22 The safety profile of sotagliflozin is generally consistent with that observed with selective SGLT2 inhibitors, except for an increased incidence of diarrhea likely associated with partial SGLT1 inhibition. 23 …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The favorable safety profile of TTP399 stands in contrast to what has been observed in trials of other promising adjunctive agents, such as sodium-glucose co-transporter 1 and 2 inhibitors and glucagon-like peptide-1 receptor agonists, for the treatment of type 1 diabetes ( 25 27 ). Although both classes improve glycemic control with placebo-adjusted changes in HbA 1c comparable to those observed with TTP399, sodium-glucose co-transporter inhibitors are associated with increased rates of ketosis and DKA, and glucagon-like peptide-1 receptor agonists are associated with increased rates of hypoglycemia and frequent hyperglycemic episodes associated with ketosis ( 25 30 ). The scarcity of AEs during treatment with TTP399 underscores the potential for TTP399 in the treatment of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, ketoacidosis adverse events result in a complete resolution in most ICSRs despite a little more of 30% had an unknown outcome that could affect the proportion of cases with a complete resolution that, therefore, cannot be perfectly estimated. Accordingly, in the literature, patients are used to restart the treatment with SGLT2 inhibitors following the resolution of the event [ 32 ]. However, we could not establish with our data if the treatment was restarted again due to our study limitations.…”
Section: Discussionmentioning
confidence: 99%